Environment and society in the long late antiquity - Izdebski, Adam; Mulryan, Michael (Late antique archaeology, 2019)
Environment and Society in the Long Late Antiquity brings together scientific, archaeological and historical evidence on the interplay of social change and environmental phenomena at the end of Antiquity and the dawn of the Middle Ages, covering the period circa 300-800 AD. It gives a new impetus to the study of the environmental history of this crucial period of transition between two major epochs in premodern history. The volume contains both systematic overviews of the previous scholarship and available data, as well as a number of interdisciplinary case studies. It covers a wide range of topics, including the histories of landscape, climate, disease and earthquakes, all intertwined with social, cultural, economic and political developments. Contributors are Daniel Abel-Schaad , Francesca Alba-Sánchez, Flavio Anselmetti, José Antonio López-Sáez, Daniel Ariztegui, Brunhilda Brushulli, Yolanda Carrión Marco, Alexandra Chavarría, Petra Dark, Carmen Fernández Ochoa, Martin Finné, Asuunta Florenzano, Ralph Fyfe,Didier Galop, Benjamin Graham, John Haldon, Kyle Harper, Richard Hodges, Adam Izdebski, Katarina Kouli, Inga Labuhn, Tamara Lewit, Anna Maria Mercuri, Alessia Masi, Lucas McMahon, Lee Mordechai, Mario Morellón, Timothy Newfield, Almudena Orejas Saco del Valle, Leonor Peña-Chocarro, Sebastián Pérez-Díaz, Eleonora Regattieri, Stephen Rippon, Neil Roberts, Laura Sadori, Abigail Sargent, Gaia Sinopoli, Paolo Squatriti, Giovanni Stranieri, Raymond van Dam, Bernd Wagner, Mark Whittow, Penelope Wilson, Jessie Woodbridge.
Keywords: Human ecology : Europe : History : To 1500; Social change : Europe : History : To 1500; Climatic changes : Social aspects : History : Europe : To 1500